Acquired Hemophilia A After Hepatic Yttrium-90 Radioembolization: A Case Report. Issue 12 (15th December 2017) - Tribuzi, Susanna; Naccarato, Alessia; Pelagalli, Lorella; Covotta, Marco; Torregiani, Giulia; Claroni, Claudia; Forastiere, Ester
Abstract : Acquired hemophilia is a rare but potentially life-threatening bleeding disorder caused by the development of autoantibodies (inhibitors) directed against plasma coagulation factors, most frequently factor VIII. We report a case of a 65-year-old man with hepatocellular carcinoma who bled massively after a hepatic Yttrium-90 radioembolization procedure (Selective Internal Radiation Therapy with Yttrium-90 Resin Microspheres [SIRTex]). An acquired deficiency of factor VIII was diagnosed and successfully treated with recombinant activated factor VII and immunosuppression.